XYLOKETAL DERIVATIVES FROM XYLARIA SP. AS STRUCTURAL LEADS FOR DUAL MYC/BCL2 AXIS MODULATION FOR DOUBLE-HIT HIGH-GRADE B-CELL LYMPHOMA: A DOCKING-BASED INVESTIGATION - Rizki Rachmad Saputra; Retno Agnestisia; Reny Rosalina; Siti Sunariyati; Yohanes Edy Gunawan (Program Studi Kimia, Fakultas MIPA, Universitas PGRI Banyuwangi, 2026)
High-grade B-cell lymphoma with concurrent MYC and BCL2 rearrangements, known as double-hit lymphoma, shows rapid tumor growth, strong resistance to apoptosis, and poor response to current therapies, largely because available treatments fail to target both oncogenic drivers at once. This study aimed to identify potential dual modulators of the MYC/BCL2 axis by evaluating xyloketal derivatives using a structure-based pharmacoinformatic approach. A total of twenty-one natural and semi-synthetic xyloketal compounds were prepared and analyzed through molecular docking against BCL2 at the BH3-binding groove (PDB: 4MAN) and the MYC/MAX heterodimer at the leucine zipper interface (PDB: 1NKP). Binding affinity, interaction profiles, and structure–activity relationships were examined using AutoDock Vina and Discovery Studio. The results showed that Xyloketal A achieved the strongest BCL2 binding affinity (−9.1 kcal/mol) while maintaining stable interactions with the MYC/MAX interface (−7.0 kcal/mol), supported by hydrogen bonding with Arg143 and Asp108 and hydrophobic contacts within the BH3 groove. Xyloketal J displayed the highest MYC/MAX affinity (−7.4 kcal/mol) with consistent BCL2 engagement, indicating a MYC-biased but still dual-target profile. Several derivatives, including Xyloketal A, Xyloketal J, and Xyloketal B cinnamyl ether, demonstrated balanced activity across both targets. These findings confirm that xyloketal scaffolds can engage both the BCL2 hydrophobic pocket and the MYC/MAX protein–protein interface, suggesting their potential as dual-target inhibitors. This study provides a clear computational foundation for the design and optimization of multi-target therapeutics aimed at overcoming the aggressive biology of double-hit high-grade B-cell lymphoma.